Cybersecurity and International Law: The Challenge of Sovereignty in Cyberspace - Md, Hefjullah (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The fast proliferation of digital networks and interconnected infrastructures has transformed cyberspace into a major sphere of geopolitical contestation, generating difficult problems about state sovereignty, jurisdiction, and responsibility. Conventional international legal systems, predicated on distinctly delineated territorial boundaries, encounter difficulties in governing actions that surpass physical borders, including cross-border cyberattacks, data breaches, and state-sponsored cyber espionage. This paper critically analyses the ways in which cybersecurity undermines traditional concepts of sovereignty and assesses the effectiveness of current international legal frameworks, such as the UN Charter, the Tallinn Manual, and regional cybersecurity conventions, in addressing matters of attribution, self-defense, and the acceptable application of force in cyber operations. The research uncovers enduring legal uncertainty regarding the definition of a cyber “attack,” the conditions under which governments may legitimately respond, and the allocation of liability for transnational cyber injuries. The study contends that sovereignty in cyberspace should be redefined as shared, layered, and cooperative, rather than solely territorial, employing doctrinal analysis and contemporary cyber incidents as case studies. It proposes that forthcoming regulatory frameworks should incorporate state accountability, multi-stakeholder governance, and standards of due diligence to promote cyber-stability. To keep cyberspace from becoming a lawless area of conflict, we need to improve international collaboration and make legal rules more consistent.